Virtues and qualities - a contribution to professionalizing the heritage professsion - Šola, Tomislav (Array, 2011)
Public memory institutions are facing challenging times: they are called upon to make their contribution, yet this cannot be done with their former "professional" attitude and their social ineptitude. Their new virtues are as old as their vices, but only relatively has their extraordinary potential become clear in terms of assisting, problem solving when applied by public memory institutions. There are many virtues, but a helpful way of convenying them is through the seven "syn-s": synthesis, synoptic, synchronism, synesthesia, synergy, synchretism, syntony.